1997
DOI: 10.1289/ehp.971051222
|View full text |Cite
|
Sign up to set email alerts
|

Triazine herbicide exposure and breast cancer incidence: an ecologic study of Kentucky counties.

Abstract: The incidence of breast cancer in the United States has steadily increased for the past three decades. Exposure to excess estrogen, in both natural and synthetic forms, has been implicated as a risk factor for the development of this disease. Considerable interest has been focused on organochlorines, such as the triazine herbicides, and their possible role in the initiation or promotion of human breast cancer. To explore this relationship, an ecologic study of Kentucky counties was designed. Exposure to triazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(55 citation statements)
references
References 26 publications
0
54
0
1
Order By: Relevance
“…Atrazine exposure during gestation can even result in prostate disease in neonatal rodents (Stanko et al, 2010). Atrazine is also associated with breast cancer (Kettles et al, 1997) and is correlated with an 8.4 fold increase in prostate cancer incidence in men working in an atrazine production facility (Maclennan et al, 2002).…”
Section: B Endocrine Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrazine exposure during gestation can even result in prostate disease in neonatal rodents (Stanko et al, 2010). Atrazine is also associated with breast cancer (Kettles et al, 1997) and is correlated with an 8.4 fold increase in prostate cancer incidence in men working in an atrazine production facility (Maclennan et al, 2002).…”
Section: B Endocrine Disruptionmentioning
confidence: 99%
“…Atrazine exposure during gestation can even result in prostate disease in neonatal rodents (Stanko et al, 2010). Atrazine is also associated with breast cancer (Kettles et al, 1997) and is correlated with an 8.4 fold increase in prostate cancer incidence in men working in an atrazine production facility (Maclennan et al, 2002).Atrazine also produces reproductive abnormalities in vertebrates under controlled laboratory conditions. For example, atrazine causes partial or complete sex reversal in fish (Tillitt et al, 2008, Suzawa andIngraham, 2008), amphibians (Hayes et al, 2002a, Hayes et al, 2006b, Hayes et al, 2010b, Hayes et al, 2002b, Hayes et al, 2002c, and reptiles (De Solla et al, 2006).…”
mentioning
confidence: 99%
“…Des questions spé cifiques se posent pour les cancers du sein, de l'ovaire, de l'uté rus, argumenté es par les perturbations endocriniennes attribué es à certains pesticides. Mê me si le rô le des organochloré s dans la survenue de cancer du sein a é té largement recherché et si certaines é tudes ont suggé ré un lien entre les triazines, et la survenue de cancer de l'ovaire [18,27], les é lé ments provenant des é tudes é pidé miologiques actuellement publié es sur ces sites de cancer sont assez peu convaincants. Les ré cents ré sultats de l'AHS montrent que chez les applicatrices de certains organophosphoré s ainsi que chez les é pouses d'agriculteurs, le risque de cancer du sein est augmenté [20].…”
Section: Limites Des é Tudes Existantes Et Perspectivesunclassified
“…Hayes et al (2002) found that, at a level as low as 0.1 ppb, atrazine causes sexual deformities in frogs. Kettles et al (1997) found a statistically significant relationship between the exposure to triazine herbicides and increased breast cancer risk in Kentucky using data on county-wide breast cancer rates. Breast cancer is the most common form of cancer among adult women in the United States (USA) Ries et al 1998) and known risk factors are thought to explain only about half of the cases occurring nationwide (Madigan et al 1995).…”
Section: Introductionmentioning
confidence: 99%